Model Internalization of Ecoliteration Values in Forming Character of Care for the Environment of Students in Fathia Islamic SD Cibeureum Sukabumi City - Aeni Latifah; Eki Agustin; Ridwan Agustian Nur (Budapest International Research and Critics University, 2022)
The research objective was to find the internalization process of ecoliteracy values in shaping the environmental care character of students at SD Islam Fahtia Cibeureum, Sukabumi City, West Java. The method used in this research is a qualitative method with a phenomenological approach. The technique of data collection was carried out by interviewing, observing and documenting with class IV, class V and class VI participants. Interviews were conducted to understand the internalization process, the strategies used in internalization and the supporting factors and obstacles to internalization. The results of this study focus on cultivating the character of caring for the environment, explaining the process of internalizing character values through the learning process in the classroom and outside the classroom such as outing classes and outbound. The strategy of planting values is integrated in thematic subjects, through both intracurricular, co-curricular and extracurricular activities with reference to the vision and mission of the school as a derivative of the original vision and mission. The supporting factors are the commitment of school institutions and programs with an environmental culture (Adiwiyata). And the ecoliteracy values that are owned are environmental awareness, empathy for the environment, and take care of oneself. The character that is emphasized in this research is the character of caring for the environment.